Protein S-Acyltransferase 14: A Specific Role for Palmitoylation in Leaf Senescence in Arabidopsis. Issue 1 (4th November 2015) - Li, Yaxiao; Scott, Rod; Doughty, James; Grant, Murray; Qi, Baoxiu
Abstract : A protein S-acyltransferase is involved in leaf senescence via modulating salicylic acid metabolism and perception. Abstract: The Asp-His-His-Cys-Cys-rich domain-containing Protein S -Acyl Transferases (PAT s) are multipass transmembrane proteins that catalyze S -acylation (commonly known as S -palmitoylation), the reversible posttranslational lipid modification of proteins. Palmitoylation enhances the hydrophobicity of proteins, contributes to their membrane association, and plays roles in protein trafficking and signaling. In Arabidopsis ( Arabidopsis thaliana ), there are at least 24 PAT s; previous studies on two PAT s established important roles in growth, development, and stress responses. In this study, we identified a, to our knowledge, novel PAT, AtPAT14, in Arabidopsis. Complementation studies in yeast ( Saccharomyces cerevisiae ) and Arabidopsis demonstrate that AtPAT14 possesses PAT enzyme activity. Disruption of AtPAT14 by T-DNA insertion resulted in an accelerated senescence phenotype. This coincided with increased transcript levels of some senescence-specific and pathogen-resistant marker genes. We show that early senescence of pat14 does not involve the signaling molecules jasmonic acid and abscisic acid, or autophagy, but associates with salicylic acid homeostasis and signaling. This strongly suggests that AtPAT14 plays a pivotal role in regulating senescence via salicylic acid pathways. Senescence is a complex process required for normal plant growth and development and requires the coordination of many genes and signaling pathways. However, precocious senescence results in loss of biomass and seed production. The negative regulation of leaf senescence by AtPAT14 in Arabidopsis highlights, to our knowledge for the first time, a specific role for palmitoylation in leaf senescence.